A newsreel history of the Third Reich. Volume 07, The meeting of the axis. [videorecording (DVD)]. (Artsmagic, 2007)
Deals with the third part of 1941. Includes the destroyers and torpedo boats on the Western Front; Rommel decorating his soldiers on the African Front; the battle for Roslaw on the Eastern Front; and Hitler and Mussolini inspecting the troops at home.